Associations between swimming & cycling abilities and fitness in 9-11 year old boys and girls. Issue 6 (19th March 2022) - Richards, Amie B.; Klos, Leon; Swindell, Nils; Griffiths, Lucy J.; De Martelaer, Kristine; Edwards, Lowri C.; Brophy, Sinead; Stratton, Gareth
ABSTRACT: The associations between swimming and cycling abilities and fitness levels in 9–11-year-old children were examined. A cross-sectional study involving 2258 children (50.7% boys; aged 10.52 ± 0.6 years) from 33 schools across Wales, participated in Swan/BridgeLinx health, fitness, and lifestyle programmes between 2013–2019. Health and fitness data were collected; namely body composition, cardiorespiratory fitness, muscular strength, flexibility, power, and speed using standardised measures. Children completed an online survey collecting data on swimming and cycling abilities and sports club attendance. Multivariate multilevel regressions were used to examine the associations between measures. The ability to swim and cycle was significantly (p < 0.05) associated with all components of fitness when accounting for age, body mass index (BMI), deprivation, gender, and sports club attendance. Boys outperformed girls with significant interactions between swimming, cycling and cardiorespiratory fitness for gender by swim (p = 0.001) and gender by cycle (p = 0.015). The gender by cycle interaction significantly predicted grip strength and power (p < 0.05). Swimming and cycling are important "milestones" in the journey of motor development and are associated with higher levels of fitness. These activities should be promoted to allow for an optimal development of motor skills, fitness, and health.